Manage Accounting in Globalization Era - Soegoto, D S; Agiva, I S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of research on the role of technology and information of globalizationera to manage accounting data is to explain the benefits and examples of information and technology in globalized economies. The method used for this research was a qualitative method, which is a research method that provides explanations using analysis. The result of this research is that globalization's rapid rise as technology grows in various aspects of life is evident, among other things in economics. Technology and information facilitate daily activities and provide many benefits to human life especially in economic matters. The research concludes that technologies and information are useful for companies to manage economic transaction data that, in turn, provide decision-making, facilitate activities where one of the advantages increases productivity, etc.